PERBEDAAN RENTANG WAKTU PERILAKU HARIAN KUNTUL KECIL (Egretta garzetta) DI KAWASAN MANGROVE ALUE NAGA KOTA BANDA ACEH - Rizky Ahadi (Biotik, 2017)
The study was conducted in May 2016, the purpose of this research to determine the difference of Egretta garzetta’s daily frequency, male and female behavior in mangrove area Alue Naga, Banda Aceh city. The method used in this study is focal animal sampling method to recording the daily behavior. Data processed using the qualitative and quantitative analysis. Analysis of the frequency of daily activity, carried out with the daily percentage. The results showed that daily behavior of Egretta garzetta include: feeding activity, perching activity, voice activity, moving activity, grooming activity, resting activity and flying activity. The highest time activity is females, that is perching and resting activity with each averaging for 70 minutes / day (28%) and 80 min / day (32%), and the lowest time span males and females is voice activity in average 1 min / day (0.4%). The conclusions derived from this research are: (1) There are 7 daily activities of Egretta garzetta in study location, include: feeding activity, perching activity, voice activity, moving activity, grooming activity, resting activity and flying activity. (2) The highest time activity is females, that is perching and resting activity.